Acute toxicity evaluation of ethanolic extract of the leaves of Anredera cordifolia in wistar rats (Rattus Norvegicus) - SURYAWATI SURYAWATI; NISSA SEURUNIE; DAMAR DITA KIRANA; VERA DEWI MULIA; HIJRA NOVIA SUARDI (Jurnal Natural, 2022)
Anredera cordifolia (Binahong) is one of the medicinal plants that has been widely used for its properties of inhibiting the growth of microorganisms, decreasing blood uric acid, and healing wounds. This study was conducted to evaluate the acute toxicity effects of ethanolic extract of binahong to support its use as a medicinal plant. Ethanolic extracts of binahong leaves were prepared. Twenty-five white male rats (Rattus norvegicus) were divided into 5 groups and administered with a single dose of Na-CMC suspension or a dose of 300, 600, 1200, or 2400 mg/kg BW of binahong ethanolic leaf extract, respectively. Toxicity symptoms were monitored at three-time intervals: ½-1, 1½-2, and 3-6 hours after the administration. A macroscopic evaluation of the rat’s liver was carried out to identify any lesion. The rat’s liver and whole-body weights were determined to assess the weight reduction. The results showed that there was no dead rat in any of the groups, indicating that no LD50 was identified. Also, there were several toxic effects observed including a decrease in movements, somatic response, insensitivity, and stool consistency. There was no evidence of a lesion on liver macroscopy. However, the weights of rats’ livers increased in tandem with the reduction in their body weights. The findings from this study reveal that single dose of binahong ethanolic extract ranging from 300 to 2400 mg/kg BW are safe, while minimal toxic effects were observed.